2017
DOI: 10.1007/s12161-017-0812-7
|View full text |Cite
|
Sign up to set email alerts
|

Fast Ion Chromatographic Method for the Determination of Formates in Alcoholic Drinks

Abstract: Monitoring of human exposure to formic acid is important due to its high biological activity. Elevated amounts of formic acid in the human body can cause serious damage to optical nerve, respiratory failure, renal failure, deep metabolic acidosis, coma, and eventual death from cardiovascular arrest. Such symptoms are characteristic for methanol poisoning owing to rapid enzymatic conversion of methanol into formic acid of substantially higher than methanol alone toxicity. Early diagnosis of methanol consumed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Primarily, to eliminate the volatile compounds from the sample solution, a raki sample was exposed to an IR source obeying the method mentioned in the literature (29). However, even though all apparatus were covered with aluminum foil, only max half of the sample could be evaporated within 3 hours.…”
Section: Matrix Eliminationmentioning
confidence: 99%
See 2 more Smart Citations
“…Primarily, to eliminate the volatile compounds from the sample solution, a raki sample was exposed to an IR source obeying the method mentioned in the literature (29). However, even though all apparatus were covered with aluminum foil, only max half of the sample could be evaporated within 3 hours.…”
Section: Matrix Eliminationmentioning
confidence: 99%
“…Also, Lachenmeier et al (34) found that there were no significant differences in anion concentrations between the same samples, which were bottled at different dates . Balcerzak and Kapica (29) analyzed formate by using the IC system. In their study, they eliminated the volatile compounds from the matrices by utilizing an infrared (IR) source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, it has been reported a variety of methods for OA separation and detection, including spectrophotometry, hydrophilic interaction liquid chromatographic (HILIC), ion chromatography, chemiluminescence, and enzymatic methods based on oxalate oxidase and oxalate decarboxylase [ 28 ]. As a powerful analytical method, ion chromatography (IC) can separate small organic acids such as FA in food and beverage samples [ 21 , 29 ]. Different detectors are used with IC, such as UV, conductivity, and mass detectors [ 21 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…This method makes it possible to detect ions of lithium, sodium, ammonium, potassium, calcium, magnesium, strontium, barium, fluorides, chlorides, nitrites, phosphates, sulfates, etc. [8][9][10][11][12] Polish scientists have developed an express method [13] for determining organic and inorganic anions in vodka and rum samples, which within 35 minutes allows you to determine the main organic and inorganic anions contained in alcoholic beverages.…”
Section: Introductionmentioning
confidence: 99%